SOSIALISASI LITERASI DIGITAL TENTANG PENGGUNAAN GADGET BIJAK UNTUK MENDUKUNG PEMBENTUKAN KARAKTER REMAJA DI SMP PLUS AL LIM DESA KARYA BHAKTI - Siti Nilam; Farida Catur Wahyu Anggriyani; Imron Ghozali; A. Dia Manda Sari; Cindy Cindy; Cindy Tri Kusuma Alam; Salsya Dwika; Elyi Dian Wisnundari; Elga Putri Asri; Anggun Citra Lukmania; Maria Nur Viona Mahwiz; Meiri Sumanti; Sulthon Arfana Zakawani; Syaiful Malik; Infan Sanjaya (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2026)
The rapid growth of digital technology has made gadgets an essential part of adolescents’ daily lives for communication, entertainment, and learning; however, uncontrolled use may reduce learning concentration, face-to-face social interaction, discipline, and character development. This community service activity aimed to improve adolescents’ knowledge and awareness of the positive and negative impacts of gadget use and to encourage more wise and responsible use. The program was implemented through an educational and participatory socialization session for Grade VII–IX students at SMP Plus Al Lim, Karya Bhakti Village, as part of the Field Work Practice (KKL) program, using material delivery, discussion, and question-and-answer activities, accompanied by observation of participant responses during the session. The results indicated positive responses, reflected in participants’ enthusiasm, active engagement in discussions, and improved understanding of gadget impacts and practical strategies for self-regulation in daily life. This activity suggests that school-based socialization as a form of community service can serve as an initial effort to support adolescent character development in the digital era and should be continued through collaboration among schools, parents, and students to achieve more sustainable outcomes.